é€šè¿‡è¯¾æ–‡ä¸Žç”Ÿè¯åˆ†æžã€ŠæˆåŠŸä¹‹è·¯ã€‹åˆçº§ç»¼åˆè¯¾æ•™æ - Fransiska, Rica; Thamrin, Lily; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The aim of this research is to know framework/principle of